Understanding the Instrument Making Process of Pemade Semar Pegulingan Saih Pitu | Memahami Proses Pembuatan Instrumen Pemade Semar Pegulingan Saih Pitu - I Wayan Agus Adi Dharma; I Made Kartawan (GHURNITA: Jurnal Seni Karawitan, 2024)
Considering the length and complexity of the process of making Balinese Gamelan, the process of learning to make instruments from bronze/kerawang is very important. Gamelan is one of the media expressed by Balinese composers in creating various musical compositions. However, before there is a composition, of course an instrument is needed as an important medium in realizing the musical idea. The process of making instruments from bronze or filigree is very interesting to learn to increase sensitivity to tones, the process of forging or forming blades, the tuning process, the process of making resonators/bumbung, and the process of making hangung/pelawah, as well as knowing the steps or stages of making instruments other. With the Internship/Practice program, it is hoped that it can awaken and maintain the enthusiasm of the next generation of young people in the field of arts and culture. Therefore, the author designed a work program with the title "From Blade to Pelawah: Understanding the Instrument Making Process of Pemade Semar Pegulingan Saih Pitu”.